Core-shell structure photocathode material for photoelectrocatalytic CO2 reduction and preparation method thereof

By constructing the Pt@Au core-shell structure on SiNWs, the problem of poor product selectivity in photoelectro-catalyzed CO2 reduction is solved, efficient CO2 reduction is achieved, and Faraday efficiency is significantly improved.

CN119640324APending Publication Date: 2025-03-18GUANGDONG UNIV OF PETROCHEMICAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411794637.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the existing photoelectrocatalytic CO2 reduction technology, SiNWs has poor selectivity for CO2 reduction products, making it difficult to improve CO2 reduction activity.

Method used

The Pt@Au/SiNWs core-shell structure photocathode material is used to promote charge separation through Pt as the core layer catalyst, and Au as the shell catalyst regulates CO2 activation, thereby improving the activity and performance of photoelectrocatalyzed CO2 reduction.

Benefits of technology

The main product that achieved CO2 reduction is CO, and its Faraday efficiency reaches 64%, which is 28 times that of pure SiNWs, significantly improving the activity and selectivity of CO2 reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640324A_ABST
    Figure CN119640324A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell structure photocathode material for photoelectrocatalysis CO2 reduction and a preparation method of the core-shell structure photocathode material, and aims to provide a core-shell structure photocathode material capable of improving photoelectrocatalysis CO2 reduction activity and a preparation method of the core-shell structure photocathode material. The photocathode material is a Pt (at) Au / SiNWs photocathode material; the preparation method of the material comprises the following steps: firstly, preparing SiNWs; the prepared SiNWs photocathode material is placed in a mixed solution containing H2PtCl6, photodeposition reduction is carried out under lamp irradiation, and finally the SiNWs photocathode material is cleaned with ultrapure water and blow-dried in the atmosphere of N2 flow to obtain Pt / SiNWs; the prepared Pt / SiNWs photocathode is placed in a mixed solution containing HAuCl4, photodeposition reduction is carried out under lamp irradiation, and finally the Pt / SiNWs photocathode is cleaned with ultrapure water and blow-dried in the atmosphere of N2 flow to obtain Pt (at) Au / SiNWs; belongs to the technical field of photoelectrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photoelectrocatalysis, and specifically relates to a core-shell structure photocathode material. The present invention also discloses a preparation method of the catalyst and its application in photoelectrocatalytic CO2 reduction. Background Art

[0002] With the development of industrialization, a large amount of fossil resources such as coal and oil have been consumed, and a large amount of CO2 gas has been emitted. As we all know, CO2 is the main greenhouse gas, which will aggravate the greenhouse effect, leading to environmental problems such as global warming and sea level rise, which will seriously threaten human survival and development. CO2 reduction to prepare chemical fuels is an effective method to realize its resource utilization. However, CO2 has the characteristics of being highly stable. Therefore, it is very challenging and difficult to activate and convert it under mild conditions.

[0003] Inspired by photosynthesis in nature, Fujishima and Honda first used SiC, GaP, TiO2 and other semiconductor materials to photocatalytically reduce CO2 to prepare organic compounds in 1979, which marked the beginning of the research on photocatalytic CO2 reduction. Subsequently, a large number of researchers have conducted explorations.

[0004] Photoelectrocatalytic technology combines the advantages of photocatalysis and electrocatalysis. It uses its photocatalytic activity to generate photogenerated electrons under illumination, reduce the input of external electron energy, and reduce energy consumption. It also uses its electrocatalytic activity to improve the selectivity and controllability of the reduction products, and can achieve photoelectric integration to a certain extent, thereby achieving high catalytic activity and high selectivity for the reduction of CO2. However, during the cathode reaction, the reduction of CO2 and H2O is a very fierce competitive reaction process. Therefore, if you want to improve the activity of CO2 reduction and the selectivity of the product, you need to design an efficient CO2 reduction photoelectrocatalyst.

[0005] Photocathode materials such as Cu2O, NiO, InP, p-Si, and Co3O4 have been applied to photoelectrocatalytic CO2 reduction. Among them, Si has a band gap width of 1.12eV, which can absorb ultraviolet light, visible light, and infrared light, and can make full use of the solar spectrum. In addition, Si also has properties such as high stability. Therefore, Si is a photocathode material with great potential. Silicon nanowires (SiNWs) are one-dimensional structures of Si, which have higher photoelectric effect, high surface activity, and electron transport properties. SiNWs have been widely used in research fields such as luminescent materials. At present, SiNWs are rarely used in the field of photoelectrocatalytic CO2 reduction because its product is mainly H2, which is generally used in research on photoelectrocatalytic hydrogen production. SiNWs have very poor product selectivity for photoelectrocatalytic CO2 reduction. Summary of the invention

[0006] In view of the above-mentioned shortcomings, the first object of the present invention is to provide a Pt@Au / SiNWs core-shell structure photocathode material that can improve the photoelectrocatalytic CO2 reduction activity.

[0007] The second object of the present invention is to provide a method for preparing the Pt@Au / SiNWs core-shell structure photocathode material.

[0008] A core-shell structure photocathode material for photoelectrocatalytic CO2 reduction, wherein the photocathode material is a Pt@Au / SiNWs photocathode material.

[0009] The second technical solution provided by the present invention is a method for preparing the core-shell structure photocathode material for photoelectrocatalytic CO2 reduction, which comprises the following steps in sequence:

[0010] Step 1) Preparation of SiNWs

[0011] 1) Clean the silicon wafer to remove impurities on the surface of the silicon wafer; then use chemical solvents to remove organic matter and oxides on the surface of the silicon wafer;

[0012] 2) placing the silicon wafer cleaned in step 1) in a mixed solution of 30 mL HF and AgNO3 to precipitate silver;

[0013] 3) Place the silver-plated silicon wafer in a mixed solution of 30 mL HF and H2O2 for etching, and then blow dry under a N2 flow atmosphere;

[0014] 4) placing the silicon wafer obtained in step 4) in a mixed solution of concentrated HNO3 and H2O, soaking to remove the Ag nanoparticles on the surface of the silicon wafer in step 3) and then washing again, then soaking in HF solution to remove the oxide layer formed on the surface of the silicon wafer, washing with ultrapure water, and drying in an atmosphere of N2 flow to obtain the SiNWs photocathode material.

[0015] Step 2) Preparation of Pt / SiNWs photocathode material

[0016] The SiNWs photocathode material prepared in step 1) was placed in a mixed solution containing H2PtCl6, and subjected to photoreduction by photodeposition for 10-120 min under irradiation of a 300W Xe Lamp. Finally, it was cleaned with ultrapure water and dried under a N2 flow atmosphere to obtain Pt / SiNWs.

[0017] Step 3) Preparation of Pt@Au / SiNWs photocathode material

[0018] The Pt / SiNWs photocathode prepared in step 2) was placed in a mixed solution containing HAuCl4, and subjected to photoreduction by photodeposition for 10-120 min under irradiation of a 300W Xe Lamp. Finally, it was cleaned with ultrapure water and dried under a N2 flow atmosphere to obtain Pt@Au / SiNWs.

[0019] Further, in the method for preparing the core-shell structure photocathode material for photoelectrocatalytic CO2 reduction, the silicon wafer is B-doped p-type silicon, the crystal plane orientation is {100}, the resistance is 1-10Ω·cm, and the silicon wafer size is 2cm 2 , thickness is 500μm.

[0020] Furthermore, in the above-mentioned method for preparing the core-shell structure photocathode material for photoelectrocatalytic CO2 reduction, the method for removing the organic substance layer and oxide on the surface of the silicon wafer in the chemical solvent described in step 1) is: placing the cleaned silicon wafer in a mixed solution of concentrated H2SO4 (mass fraction of 98%) and H2O2 (mass fraction of 35%) in a volume ratio of 3:1, soaking for 60 minutes, further removing the organic substance layer and oxide on the surface of the silicon wafer, and then washing the silicon wafer with a large amount of ultrapure water to remove the H2SO4 and H2O2 on the surface of the silicon wafer.

[0021] Furthermore, the preparation method of the core-shell structure photocathode material for photoelectrocatalytic CO2 reduction mentioned above, wherein the cleaned silicon wafer (the silicon wafer size is 2 cm 2,厚度 500μm) was placed in a mixed solution of 30mL4.9M HF and 0.005MAgNO3 and stirred slowly for 1min to precipitate silver.

[0022] Furthermore, the preparation method of the core-shell structure photocathode material for photoelectrocatalytic CO2 reduction is as follows: the silver-plated silicon wafer is placed in a mixed solution of 30mL4.6M HF and 0.5-0.9M H2O2, slowly stirred for 45 minutes, taken out and immediately washed with a large amount of ultrapure water, and blown dry in an atmosphere of N2 flow.

[0023] Furthermore, in the above-mentioned method for preparing the core-shell structure photocathode material for photoelectrocatalytic CO2 reduction, the volume ratio of concentrated HNO3 and H2O is 1:1; and the HF solution is a 5% by mass HF aqueous solution.

[0024] Furthermore, in the above-mentioned method for preparing the core-shell structure photocathode material for photoelectrocatalytic CO2 reduction, the mixed solution containing H2PtCl6 is prepared by mixing 45mLH2O, 5mL methanol, and 200μL 10mMH2PtCl6.

[0025] Furthermore, in the above-mentioned method for preparing the core-shell structure photocathode material for photoelectrocatalytic CO2 reduction, the mixed solution containing HAuCl4 is prepared by mixing 45mLH2O, 5mL methanol, and 200μL 10mM HAuCl4.

[0026] Compared with the prior art, the technical solution provided by the present invention has the following technical advantages:

[0027] 1. The technical solution provided by the present invention adopts SiNWs as the substrate material. SiNWs is a one-dimensional nanostructure of Si. Compared with bulk Si, it has more excellent properties, such as optical properties such as photoelectric effect, high surface activity, electron transport characteristics, etc., and also has higher stability.

[0028] 2. In the Pt@Au / SiNWs photocathode material provided by the present invention, Pt as a core catalyst can promote charge separation, and Au as a shell catalyst can regulate the activation of CO2, thereby improving the activity and performance of photoelectrocatalytic CO2 reduction. The main product of the photoelectrocatalytic CO2 reduction of the Pt@Au / SiNWs photocathode material is CO, and its Faraday efficiency reaches 64%, which is 28 times that of pure SiNWs.

[0029] 3. The Pt@Au / SiNWs photocathode material provided by the present invention can provide theoretical guidance for the preparation of photoelectrocatalysts with high catalytic activity and high product selectivity, thereby establishing an efficient photoelectrocatalytic CO2 reduction system and further realizing efficient resource utilization of CO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a SEM image of Pt@Au / SiNWs provided in Example 1;

[0031] Figure 2 is a TEM image of Pt@Au / SiNWs provided in Example 1;

[0032] Figure 3 This is a comparison of the CO Faraday efficiency of the photoelectrocatalytic CO2 reduction products of different photocathode materials. DETAILED DESCRIPTION

[0033] The claims of the present invention are further described in detail below in conjunction with specific implementations and accompanying drawings, but do not constitute any limitation to the present invention.

[0034] The silicon wafer used in the following examples is p-type silicon (B doped), with a crystal plane orientation of {100}, a resistance of 1-10Ω·cm, and a size of 2cm 2, The thickness is 500μm.

[0035] Example 1

[0036] Step 1) Preparation of SiNWs

[0037] 1) Using acetone, anhydrous ethanol, and ultrapure water in sequence, ultrasonically clean the silicon wafer at a power of 100 W for 15 minutes to remove pollutants on the surface of the silicon wafer;

[0038] 2) Soak the cleaned silicon wafer in a mixed solution of concentrated H2SO4 (98% by mass): H2O2 (35% by mass) in a volume ratio of 3:1 for 60 minutes to further remove the organic material layer and oxide on the surface of the silicon wafer, and then wash the silicon wafer with a large amount of ultrapure water to remove H2SO4 and H2O2 on the surface of the silicon wafer;

[0039] 3) Place the cleaned silicon wafer in a mixed solution of 30 mL 4.9 M HF and 0.005 M AgNO3, slowly stir for 1 min, and perform silver precipitation;

[0040] 4) Place the silver-deposited silicon wafer in a 30 mL mixed solution of 4.9 M HF and 0.5 M H2O2, slowly stir for 45 min, take it out and immediately wash it with a large amount of ultrapure water, and blow it dry under a N2 flow atmosphere;

[0041] 5) The silicon wafer obtained in step 4) is placed in a mixed solution of concentrated HNO3:H2O with a volume ratio of 1:1 and soaked for 60 minutes to remove all the Ag nanoparticles on the surface of the silicon wafer and the bottom of the SiNWs. After taking it out, it is immediately washed with a large amount of ultrapure water, and then the cleaned silicon wafer is placed in a 5% HF solution and soaked for 5 minutes to remove the oxide layer formed on the surface of the silicon wafer. It is cleaned with a large amount of ultrapure water and blown dry in an atmosphere of N2 flow to obtain the SiNWs photocathode material.

[0042] Step 2) Preparation of Pt / SiNWs photocathode material

[0043] The SiNWs photocathode material prepared in step 1) was placed in a mixed solution, wherein the mixed solution was mixed with 45 mL H2O, 5 mL methanol and 200 μL 10 mM H2PtCl6, and photoreduction was performed for 60 min under 300 W Xe Lamp irradiation. Finally, it was cleaned with ultrapure water and dried under N2 flow atmosphere to obtain Pt / SiNWs.

[0044] Step 3) Preparation of Pt@Au / SiNWs photocathode material

[0045] The Pt / SiNWs photocathode prepared in step 2) was placed in a mixed solution consisting of 45 mL H2O, 5 mL methanol, and 200 μL 10 mM HAuCl4. Under irradiation with a 300 W Xe Lamp, photoreduction was performed for 60 min. Finally, it was cleaned with ultrapure water and dried under a N2 flow atmosphere to obtain Pt@Au / SiNWs.

[0046] The SEM image of Pt@Au / SiNWs prepared in Example 1 is shown in Figure 1 , TEM image see Figure 2 It can be seen from the figure that Pt and Au nanoparticles are successfully loaded on SiNWs with good morphology and core-shell structural characteristics.

[0047] Example 2

[0048] Step 1) Preparation of SiNWs

[0049] 1) Using acetone, anhydrous ethanol, and ultrapure water in sequence, ultrasonically clean the silicon wafer at a power of 100 W for 15 minutes to remove pollutants on the surface of the silicon wafer;

[0050] The silicon wafer is p-type silicon (B doped), with a crystal plane orientation of {100}, a resistance of 1-10Ω·cm, and a thickness of 500μm;

[0051] 2) Soak the cleaned silicon wafer in a mixed solution of concentrated H2SO4 (98% by mass): H2O2 (35% by mass) in a volume ratio of 3:1 for 60 minutes to further remove the organic material layer and oxide on the surface of the silicon wafer, and then wash the silicon wafer with a large amount of ultrapure water to remove H2SO4 and H2O2 on the surface of the silicon wafer;

[0052] 3) Place the cleaned silicon wafer in a mixed solution of 30 mL 4.9 M HF and 0.005 MAgNO3, slowly stir for 1 min, and perform silver precipitation;

[0053] 4) Place the silver-deposited silicon wafer in a 30 mL mixed solution of 4.9 M HF and 0.9 M H2O2, slowly stir for 45 min, take it out and immediately wash it with a large amount of ultrapure water, and blow it dry under a N2 flow atmosphere;

[0054] 5) The silicon wafer obtained in step 4) is placed in a mixed solution of concentrated HNO3:H2O with a volume ratio of 1:1 and soaked for 60 minutes to remove all the Ag nanoparticles on the surface of the silicon wafer and the bottom of the SiNWs. After taking it out, it is immediately washed with a large amount of ultrapure water, and then the cleaned silicon wafer is placed in a 5% HF solution and soaked for 5 minutes to remove the oxide layer formed on the surface of the silicon wafer. It is cleaned with a large amount of ultrapure water and blown dry in an atmosphere of N2 flow to obtain the SiNWs photocathode material.

[0055] Step 2) Preparation of Pt / SiNWs photocathode material

[0056] The SiNWs photocathode material prepared in step 1) was placed in a mixed solution, wherein the mixed solution was mixed with 45 mL H2O, 5 mL methanol and 200 μL 10 mM H2PtCl6, and photoreduction was performed for 60 min under 300 W Xe Lamp irradiation. Finally, it was cleaned with ultrapure water and dried under N2 flow atmosphere to obtain Pt / SiNWs.

[0057] Step 3) Preparation of Pt@Au / SiNWs photocathode material

[0058] The Pt / SiNWs photocathode prepared in step 2) was placed in a mixed solution, wherein the mixed solution was mixed with 45 mL H2O, 5 mL methanol, and 200 μL 10 mM HAuCl4, and photoreduction was performed for 120 min under irradiation of a 300 W Xe Lamp. Finally, it was cleaned with ultrapure water and dried under a N2 flow atmosphere to obtain Pt@Au / SiNWs.

[0059] Comparative Example 1

[0060] This comparative example provides an Au / SiNWs, which is prepared by the following steps:

[0061] Step 1) Preparation of SiNWs

[0062] This step is exactly the same as step 1) in Example 1.

[0063] Step 2) Preparation of Au / SiNWs photocathode material

[0064] This step is basically the same as step 2) of Example 1; the difference is that an equal amount of HAuCl4 is used instead of H2PtCl6 to obtain Au / SiNWs.

[0065] In order to demonstrate the performance of the technical solution provided in the present application, the photoelectrocatalytic CO2 reduction performance test of the Pt@Au / SiNWs photocathode material is given below.

[0066] Test Example 1

[0067] The reaction device for photoelectrocatalytic CO2 reduction is based on the structure of proton exchange membrane fuel cells and adopts an H-type dual-cell structure. Its structure is divided into a cathode chamber and an anode chamber, and the electrolyte is 50mL 0.1KHCO3. In the cathode chamber, the Pt@Au / SiNWs photocathode prepared in Example 1 is used as the working electrode, and Ag / AgCl filled with saturated KCl solution is used as the reference electrode; in the anode chamber, a platinum sheet (1×1cm 2 ) was the counter electrode. The voltage during the experiment was controlled by an electrochemical workstation (CHI660E). Before the reaction, CO2 gas was continuously introduced for more than 60 min to saturate the solution with CO2 and a pH of about 6.8. The light source was a xenon lamp with a power of 300 W. AM 1.5G filter was used and the light intensity was controlled to be 100 mW cm -2 At a voltage of -1.4V vs.Ag / AgCl, after a certain reaction time, the gas phase product generated at the cathode was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance. The main product of CO2 reduction catalyzed by Pt@Au / SiNWs photocathode material is CO, and its Faraday efficiency reaches 64%.

[0068] Comparative test example 1

[0069] The method and process parameters used in this test example are consistent with those of Comparative Example 1, except that the SiNWs photocathode material prepared in step 1) of Example 1 is used instead of the Pt@Au / SiNWs photocathode prepared in Example 1 as the working electrode. After testing, the main products of the catalytic CO2 reduction of the SiNWs photocathode material are H2 and a small amount of CO, where the Faraday efficiency of CO is 2.3%.

[0070] Comparative test example 2

[0071] The method and process parameters used in this test example are consistent with those of Comparative Example 1, except that the Au / SiNWs photocathode material prepared in Comparative Example 1 replaces the Pt@Au / SiNWs photocathode prepared in Example 1 as the working electrode; after testing, the main products of the catalytic CO2 reduction of the Au / SiNWs photocathode material are H2 and CO, of which the Faraday efficiency of CO is 21%.

[0072] Through the above test example 1, test comparative examples 1 and 2 test data and Figure 3 It can be seen that the Faradaic efficiency of the Pt@Au / SiNWs photocathode material provided in the present application for catalyzing the reduction of CO2 to prepare CO is 28 times the Faradaic efficiency of the SiNWs photocathode material for catalyzing the reduction of CO2 to prepare CO, and is 3.0 times the Faradaic efficiency of the Au / SiNWs photocathode material for catalyzing the reduction of CO2 to prepare CO.

Claims

1. A core-shell structure photocathode material for photoelectrocatalytic CO2 reduction, characterized in that: The photocathode material is Pt@Au / SiNWs photocathode material.

2. The method for preparing a core-shell structure photocathode material for photoelectrocatalytic CO2 reduction according to claim 1, characterized in that: The steps are as follows: Step 1) Preparation of SiNWs 1) Clean the silicon wafer to remove impurities on the surface of the silicon wafer; then remove the organic material layer and oxide on the surface of the silicon wafer by chemical solvent; 2) placing the silicon wafer cleaned in step 1) in a mixed solution of HF and AgNO3 to precipitate silver; 3) Place the silver-plated silicon wafer in a mixed solution of HF and H2O2 for etching, and then blow dry in an atmosphere of N2 flow; 4) placing the silicon wafer obtained in step 4) in a mixed solution of concentrated HNO3 and H2O, soaking to remove the Ag nanoparticles on the surface of the silicon wafer in step 3) and then washing again, then soaking in HF solution to remove the oxide layer formed on the surface of the silicon wafer, washing with ultrapure water, and drying in an atmosphere of N2 flow to obtain the SiNWs photocathode material. Step 2) Preparation of Pt / SiNWs photocathode material The SiNWs photocathode material prepared in step 1) is placed in a mixed solution containing H2PtCl6, and subjected to photoreduction by photodeposition for 10-120 minutes under lamp irradiation. Finally, it is cleaned with ultrapure water and blown dry in an atmosphere of N2 flow to obtain Pt / SiNWs. Step 3) Preparation of Pt@Au / SiNWs photocathode material The Pt / SiNWs photocathode prepared in step 2) was placed in a mixed solution containing HAuCl4, and subjected to photoreduction by photodeposition for 10-120 min under irradiation of a 300W Xe Lamp. Finally, it was cleaned with ultrapure water and dried under a N2 flow atmosphere to obtain Pt@Au / SiNWs.

3. The method for preparing a core-shell structure photocathode material for photoelectrocatalytic CO2 reduction according to claim 2, characterized in that: The silicon wafer is B-doped p-type silicon, with a crystal plane orientation of {100}, a resistance of 1-10Ω·cm, and a thickness of 500μm.

4. The method for preparing a core-shell structure photocathode material for photoelectrocatalytic CO2 reduction according to claim 2, characterized in that: The method for removing the organic substance layer and oxide on the surface of the silicon wafer in the chemical solvent described in step 1) is: placing the cleaned silicon wafer in a mixed solution of concentrated H2SO4 and H2O2 with a volume ratio of 3:1, soaking for 60 minutes, further removing the organic substance layer and oxide on the surface of the silicon wafer, and then washing the silicon wafer with a large amount of ultrapure water to remove H2SO4 and H2O2 on the surface of the silicon wafer.

5. The method for preparing a core-shell structure photocathode material for photoelectrocatalytic CO2 reduction according to claim 2, characterized in that: The cleaned 2cm 2 The silicon wafer was placed in a mixed solution of 30 mL 4.9 M HF and 0.005 M AgNO3 and stirred slowly for 1 min to precipitate silver.

6. The method for preparing a core-shell structure photocathode material for photoelectrocatalytic CO2 reduction according to claim 2, characterized in that: The above is to put the 2cm after silver sinking 2 The silicon wafer was placed in 30 mL of a mixed solution of 4.6 M HF and 0.5-0.9 M H2O2 and stirred slowly for 45 min. The wafer was taken out and immediately washed with a large amount of ultrapure water and dried under a N2 flow atmosphere.

7. The method for preparing a core-shell structure photocathode material for photoelectrocatalytic CO2 reduction according to claim 2, characterized in that: The volume ratio of the concentrated HNO3 and H2O is 1:1; the HF solution is a 5% HF aqueous solution by mass.

8. The method for preparing a core-shell structure photocathode material for photoelectrocatalytic CO2 reduction according to claim 2, characterized in that: The mixed solution containing H2PtCl6 is prepared by mixing 45mL H2O, 5mL methanol, and 200μL 10mM H2PtCl6.

9. The method for preparing a core-shell structure photocathode material for photoelectrocatalytic CO2 reduction according to claim 2, characterized in that: The mixed solution containing HAuCl4 is prepared by mixing 45 mL H2O, 5 mL methanol, and 200 μL 10 mM HAuCl4.